Science Patronage, the Rockefeller Foundation, and the Mexican Social Sciences in the 1940s - Álvaro Morcillo Laiz (Estudios Sociológicos, 2023)
If the public universities of Latin America are considered part of the State, then it would seem likely that they share fundamental features with it. This would imply, for example, that during much of the 20th century, universities have been clientelistic, like the State itself. However, this feasible hypothesis has never been examined by the literature on the Mexican social sciences of the 20th century. The same is true of the role played by patrons of science, such as American philanthropic foundations. In this article, I argue that the Rockefeller Foundation sponsored the humanities, practiced in a liberal spirit, and organized according to formal rational criteria; the Foundation wished to promote an alternative to what it perceived as clientelism and amateurism in Latin American universities. While philanthropic foundations have often been seen as yet another manifestation of how U.S. imperialism pursues cultural hegemony in Latin America, this article shows that foundations were neither individual actors nor able to predict the actual impact of their decisions. In Mexico, the Rockefeller Foundation promoted the humanities in the 1940s, but missed the opportunity to support a local vision of social science teaching and research.